The Da Vinci code a novel (New York Anchor, 2006)
A Harvard symbologist is called in to assist the investigation into the murder of a Louvres curator and discovers a trail of clues in the Da Vinci paintings put there by the painter himself!
Keywords: Leonardo, -- da Vinci -- 1452-1519 -- Manuscripts -- Fiction; Cryptographers -- Fiction; Suspense fiction